1997
DOI: 10.1080/00332747.1997.11024781
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Severe Mental Disorder in Clinical and Community Populations: The Effects of Psychotic Symptoms, Comorbidity, and Lack of Treatment

Abstract: This paper examines links between violent behavior, type and severity of psychopathology, substance abuse comorbidity, and community mental health treatment, using matched data from two surveys: the National Institute of Mental Health Epidemiologic Catchment Area project and the Triangle Mental Health Survey (a North Carolina study of adults with severe and persistent mental illness). Multivariate logistic regression analysis was used to model the risk of violent acts attributable to three domains of independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(134 citation statements)
references
References 17 publications
7
121
0
6
Order By: Relevance
“…Thus, psychotic states and drug intoxication may each contribute independently to violent behaviour by producing abnormalities in perception and cognition and perhaps impulse control. But it is also plausible that psychoactive substance use may contribute to violence indirectly, in at least four other ways; first, by contributing (earlier in life) to the development of concurrent antisocial personality disorder which is often characterised by violent behaviour; second, by exacerbating or compounding chronic psychotic symptomalology which is already present in persons with mental disorder; third, by drawing such persons into threatening and hostile social environments in which violent crime and other social pathologies are more common; and fourth, by rendering them less responsive to, and less compliant with, outpatient medication therapies and other community-based mental health services which might otherwise prevent violence (see Drake, Bartels, Teague, Noordsy & Clark, 1993;Widiger & Trull, 1994;Owen, Fischer, Booth & Cuffel, 1996;Swanson, Estroff, Swartz, Borum, Lachicotte, Zimmer & Wagner, 1997).…”
Section: New Evidencementioning
confidence: 98%
“…Thus, psychotic states and drug intoxication may each contribute independently to violent behaviour by producing abnormalities in perception and cognition and perhaps impulse control. But it is also plausible that psychoactive substance use may contribute to violence indirectly, in at least four other ways; first, by contributing (earlier in life) to the development of concurrent antisocial personality disorder which is often characterised by violent behaviour; second, by exacerbating or compounding chronic psychotic symptomalology which is already present in persons with mental disorder; third, by drawing such persons into threatening and hostile social environments in which violent crime and other social pathologies are more common; and fourth, by rendering them less responsive to, and less compliant with, outpatient medication therapies and other community-based mental health services which might otherwise prevent violence (see Drake, Bartels, Teague, Noordsy & Clark, 1993;Widiger & Trull, 1994;Owen, Fischer, Booth & Cuffel, 1996;Swanson, Estroff, Swartz, Borum, Lachicotte, Zimmer & Wagner, 1997).…”
Section: New Evidencementioning
confidence: 98%
“…Nearly 90% (27/31) of the studies of perpetration that we reviewed sampled patients from clinics or hospitals (11,12,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(46)(47)(48)(49)(50)(51); among studies that examined prevalence of victimization, all sampled persons in treatment. We need information on the estimated 5 million persons with severe mental illness in the United States who do not receive treatment (67).…”
Section: Investigate Community Populations Not Only Persons In Treatmentioning
confidence: 99%
“…[32][33] Certain psychotic symptoms, such as delusions of persecution 34 and auditory hallucinations, 33 have been shown to be more strongly associated with violent behavior. However, other authors have found no association between active psychotic symptoms and violent behavior.…”
Section: Schizophrenia Schizoaffective Disorder and Delusional Disordermentioning
confidence: 99%